2018
DOI: 10.1089/scd.2018.0023
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Promotes Osteoblast Differentiation in Human Mesenchymal Stem Cells Via Activation of the cAMP-PKA-CREB Signaling Pathway

Abstract: The crucial trace element zinc stimulates osteogenesis in vitro and in vivo. However, the pathways mediating these effects remain poorly understood. This study aimed to investigate the effects of zinc on osteoblast differentiation in human bone marrow-derived mesenchymal stem cells (hBMSCs) and to identify the molecular mechanisms of these effects. In hBMSCs, zinc exposure resulted in a dose-dependent increase in osteogenesis and increased mRNA and protein levels of the master transcriptional factor RUNX2. Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(83 citation statements)
references
References 51 publications
6
77
0
Order By: Relevance
“…45,46 Also, it has been proved that zinc exerts osteogenic effects on hBMSCs by increasing mRNA and protein levels of the master transcriptional factor RUNX2. 13 In conclusion, it can be inferred that the appropriate Zn 2+ microenvironments (2-5 mg mL À1 ) induce the osteogenic differentiation of rBMSCs by activating the MAPK/ERK signaling pathway; while higher concentration (15 mg mL À1 ) of Zn 2+ inhibits that signaling pathway and osteogenic differentiation. These ndings may clarify the underlying mechanism on osteogenic differentiation regulated by diverse Zn 2+ microenvironments in both positive and negative aspects.…”
Section: Positive and Negative Regulation Of Zn 2+ Microenvironmentsmentioning
confidence: 86%
See 2 more Smart Citations
“…45,46 Also, it has been proved that zinc exerts osteogenic effects on hBMSCs by increasing mRNA and protein levels of the master transcriptional factor RUNX2. 13 In conclusion, it can be inferred that the appropriate Zn 2+ microenvironments (2-5 mg mL À1 ) induce the osteogenic differentiation of rBMSCs by activating the MAPK/ERK signaling pathway; while higher concentration (15 mg mL À1 ) of Zn 2+ inhibits that signaling pathway and osteogenic differentiation. These ndings may clarify the underlying mechanism on osteogenic differentiation regulated by diverse Zn 2+ microenvironments in both positive and negative aspects.…”
Section: Positive and Negative Regulation Of Zn 2+ Microenvironmentsmentioning
confidence: 86%
“…Conforming to our results, it was reported that Zn 2+ concentration of 25 mM (1.6 mg mL À1 ) promoted the proliferation of MC3T3-E1 cells, 39 but ZnSO 4 concentration of 200 mM (Zn 2+ 13 mg mL À1 ) inhibited the proliferation of hBMSCs. 13 Therefore, only the Zn 2+ microenvironments with appropriate concentrations can promote cell proliferation of osteoblast and BMSCs, with too low concentration of Zn 2+ having no biological effects and too high concentration inducing cytotoxicity. Recent studies have indicated that zinc-loaded biomaterials also have a concentration-dependent effect on cell proliferation.…”
Section: Double-edged Effects Of Zn 2+ Microenvironments On Rbmscs VImentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the nature of the growth factors, these factors can induce sustained changes on stem cells at the genetic and epigenetic levels that cause the patient faced with more problems (Lunyak & Rosenfeld, 2008;Olynik & Rastegar, 2012). Many studies have been tried to introduce alternative factors form herbal or other biological sources to be useable in the orthopedics clinics (Akbarzadeh et al, 2014;Lee, Uddin, Kim, Choi, & Park, 2017;Mofid et al, 2015;K. H. Park et al, 2018;Udalamaththa, Jayasinghe, & Udagama, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the phosphorylation state of the transcription factor CRE-binding protein (CREB) promotes the expression of MITF by binding to and activating the promoter of MITF, thereby promoting the activation of MC function (Alam et al, 2018;Shin et al, 2018). The transcription factor CREB is regulated by a variety of signaling pathways, among which are confirmed pathways such as the cAMP/protein kinase A (PKA) (Park et al, 2018;Xie et al, 2018), mitogen-activated protein kinase (MAPK) family (Fujimura and Usuki, 2018;Yu et al, 2019), Ca 2þ /CaMK (Chen et al, 2018a;Liu et al, 2018), and PI3K/Akt signaling pathways (Dong et al, 2018;Nishina et al, 2018). The cAMP/PKA signaling pathway is one of the key regulatory pathways that promotes the activation of MITF (Choi et al, 2018;Sun et al, 2017).…”
Section: Introductionmentioning
confidence: 99%